Diagnosis of acute myocardial infarction in the emergency setting - Seema Bhargava; Anjali Manocha; Mamta Kankra; L M Srivastava (Current Medicine Research and Practice, 2013)
Acute coronary syndrome (ACS) in the emergency setting poses a dilemma in its differential diagnosis. It encompasses a range of thrombotic coronary events including acute myocardial infarction (AMI) and unstable angina. The line of management depends upon whether or not the patient has AMI, and one of the factors affecting morbidity is the time of initiation of treatment after onset of symptoms. Hence, it is important to differentiate between AMI and unstable angina. Since ECG alone has a low sensitivity and specificity for AMI, biochemical serum markers (AST, CPK, CKMB mass, troponins, myoglobin) are used to aid diagnosis. As newer biomarkers evolve and methodologies improve, guidelines for the diagnosis of AMI have also been revised. In 2012, the European Society of Cardiology (ESC) and American College of Cardiology (ACC) have suggested guidelines for the diagnosis of AMI. Taking into consideration these guidelines, and the pathophysiology of cardiac biomarkers, an algorithm has been suggested for the diagnosis of AMI in patients presenting to the emergency department within 10 hours of onset of chest pain. This would aid in early and accurate diagnosis of AMI.